2007
DOI: 10.1097/inf.0b013e31814614c6
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of a Pneumococcal Conjugate 7-Valent Vaccine in Infants With Sickle Cell Disease

Abstract: PCV7 administered at 2, 3, and 4 months of age in infants with SCD was well-tolerated, highly immunogenic, and primed for immune memory as indicated by the dramatic response to the PS-23 dose administered at 15-18 months in this study. However, the current recommended schedule is to boost with the PCV7 at 12-15 months of age and for these high-risk children, to enlarge the protection with a subsequent PS-23 dose at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…While analyzing potential determinants affecting the antibody response to vaccination, we showed that pre‐OLT titers were strongly predictive of post‐OLT titers. This was the case for all antigens except SPn23, maybe because it is the less immunogenic of the tested pneumococcal serotypes (26). Moreover, and even if this never reached significance in our cohort, patients with protective titers one yr post‐OLT had higher pre‐OLT titers than those without protective titers.…”
Section: Discussionmentioning
confidence: 89%
“…While analyzing potential determinants affecting the antibody response to vaccination, we showed that pre‐OLT titers were strongly predictive of post‐OLT titers. This was the case for all antigens except SPn23, maybe because it is the less immunogenic of the tested pneumococcal serotypes (26). Moreover, and even if this never reached significance in our cohort, patients with protective titers one yr post‐OLT had higher pre‐OLT titers than those without protective titers.…”
Section: Discussionmentioning
confidence: 89%
“…MRI/MRA (n ϭ 463) were performed in 132 SCA patients. The median number of MRI/MRA per patient was 2 (range, [1][2][3][4][5][6][7][8]. In patients older than 5 years, MRI/MRA without sedation failed in 2 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the participants, grouped as SCA (n ϭ 217: 209 SS, 6 S␤ 0 , 2 SD-Punjab), are summarized in Table 1. A total of 1351 TCD were performed at annual check-ups, with a median number of TCD/patient of 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. MRI/MRA (n ϭ 463) were performed in 132 SCA patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations